Pemurnian Selulosa Alfa Pelepah Sawit Menggunakan Enzim Xylanase - Caesari Caesari; Padil Padil; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Midrib of palm oil is the most solid wastes which produced in oil palm plantations. Palm midrib is contained of 34.89% α-cellulose content percentage that can be improved with cooking using the extract solution ash of palm empty fruit bunches (Padil, 2010) and continued with the process of purification using xylanase enzyme. Higher content of Cellulose-α can be processed into a more commercially product. Cellulose-α> 92% qualified to be used as the main raw material (nitrocellulose) or making explosives and propellants. Stages of the purification process a palm midrib cellulose is extraction, hydrolysis, delignification and purification using xylanase enzyme with variations process is temperature (50, 60 and 70 ° C), enzyme dose (1, 2 and 3 ml) and the source of the enzyme (Aspergillus and Trichoderma sp so). Purification process operating conditions are: pH 5, time 90 minutes, the solid-solution 1:25. Content of purified cellulose-α increased to 96.60% for variable temperature at 60 ° C, 3 ml dose of enzymes and enzyme xylanase from Aspergillus sp. Keywords : Cellulose Alpha, Palm Midrib, Xylanase Enzyme